1999
DOI: 10.1080/026990599121016
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine responses following graded traumatic brain injury in male adults

Abstract: In an effort to characterize thyroid, gonadal and adrenal function following neurotrauma, the present study determined serum concentrations of thyroid-stimulating hormone (TSH), total triiodothyronine (T3), thyroxine (T4), testosterone and cortisol over a 7 day period in 31 patients with traumatic brain injury. The study group consisted of eight patients with mild closed head injury (Glasgow Coma Scale--GCS 13-15), 10 patients with extensive penetrating head injury (GCS 4-6) and 13 patients with blast injuries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(23 citation statements)
references
References 23 publications
3
19
1
Order By: Relevance
“…Hyponatremia was previously thought to be primarily due to SIADH [7,49], with acute ACTH deficiency felt to be a relatively rare entity. However, almost all previous studies relied on assessment of cortisol dynamics at a single time point, providing only a “snapshot” of patients’ pituitary function [50,51,52,53,54,55,56]. Plasma cortisol levels are highly dynamic in the days following TBI [51,52], so protocols with only a single time point for testing may underestimate the true incidence of pituitary dysfunction immediately following TBI.…”
Section: Hyponatremia Following Traumatic Brain Injurymentioning
confidence: 99%
“…Hyponatremia was previously thought to be primarily due to SIADH [7,49], with acute ACTH deficiency felt to be a relatively rare entity. However, almost all previous studies relied on assessment of cortisol dynamics at a single time point, providing only a “snapshot” of patients’ pituitary function [50,51,52,53,54,55,56]. Plasma cortisol levels are highly dynamic in the days following TBI [51,52], so protocols with only a single time point for testing may underestimate the true incidence of pituitary dysfunction immediately following TBI.…”
Section: Hyponatremia Following Traumatic Brain Injurymentioning
confidence: 99%
“…As for the subacute period, studies suggest that plasma cortisol levels are dependent on the injury severity. Cortisol tends to increase after mild to moderate brain injury in the early post-injury period, whereas it is depressed after a severe injury [ 82, 83 ]. Although structural pituitary damage may be dependent on the severity of the injury [ 84 ], pituitary abnormalities have been reported in mild to moderate injuries.…”
Section: Impaired/abnormal Activation After Tbimentioning
confidence: 99%
“…Among these, a retrospective cohort study by Majerske found that high levels of cognitive and physical activity during the early postinjury period had a negative effect on cognitive function and were associated with worsened concussive symptoms and performance on cognitive testing [ 162 ] [Majerske J Athl Training 2008]. The occurrence of negative mood states and cognitive impairments may be associated with neuroendocrine alterations that are found in the early post-TBI weeks, such as elevated plasma cortisol levels [ 83 ].…”
Section: Timing Of Return To Activitymentioning
confidence: 99%
“…Injury-induced endocrine dysfunction can be concomitant with and potentially augment clinical symptoms commonly associated with postconcussive syndrome and post-traumatic stress disorder (PTSD) (22, 29). While the prevalence of endocrine dysfunction is reported in the clinical literature, few experimental models have elucidated the persistence and pathological basis of mild-moderate diffuse brain injury-induced endocrine dysfunction (9, 30). …”
Section: Introductionmentioning
confidence: 99%